Hubungan Self Efficacy Terhadap Motivasi Belajar Biologi Kelas VII SMP Negeri 25 Pekanbaru Tahun Ajaran 2023/2024 - Intan Regina Fatimah Az-Zahra; Nurul Fauziah (Pendekar : Jurnal Pendidikan Berkarakter, 2024)
The research was motivated by the low learning motivation of the remaining students at SMP Negeri 25 Pekanbaru. The purpose of this research was to determine the relationship between Self Efficacy and students' biology learning motivation. The research method used in this research is the correlational method, using a saturated sampling technique, which is a sample determination technique if all members of the population are sampled. The sample in this study was 90 students. The data collection instrument uses a questionnaire. Based on the significant test (t test) is obtained tcount > ttable is 14,464 > 1,987. This means that there is a significant relationship between learning motivation and self-efficacy. The R2 (R square) value based on the test results is 0.704 or 70.392%. This shows that 70.392% of learning motivation variables are influenced by self-efficacy. The variance in the model's independent variable (self efficacy) can reach 70.392% of the variance in the dependent variable (learning motivation). So it is concluded that there is a relationship between self-efficacy and student learning motivation at SMP Negeri 25 Pekanbaru for the 2023/2024 academic year in the strong category.